2009
DOI: 10.3112/erdkunde.2009.04.04
|View full text |Cite
|
Sign up to set email alerts
|

Climatic control of radial growth of Cedrela montana in a humid mountain rainforest in southern Ecuador

Abstract: Cedrela montana is a deciduous broad-leaved tree species growing in the humid mountain rainforests of southern Ecuador. High-resolution dendrometer data indicate a regular seasonal growth rhythm with cambial activity during January to April. Amplitudes of daily radial stem diameter variations are correlated with the amount of the maximum daily vapour pressure deficit. During humid periods, daily stem diameter variations are considerably smaller than during drier periods. This indicates that cambial activity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 34 publications
8
33
0
6
Order By: Relevance
“…While the aim of this review is not to extensively describe and discuss these techniques, we briefly mention them. A first technique to evaluate the annual character of ring formation involves measuring the periodicity of tree growth through dendrometer measurements (Bräuning et al 2009;Krepkowski et al 2010;Volland-Voigt et al 2010). By measuring stem diameter increase and shrinkage over the seasons, insight in intra-annual growth dynamics can be obtained.…”
Section: Periodicity In Tree Growth and Detection Of Tropical Tree Ringsmentioning
confidence: 99%
“…While the aim of this review is not to extensively describe and discuss these techniques, we briefly mention them. A first technique to evaluate the annual character of ring formation involves measuring the periodicity of tree growth through dendrometer measurements (Bräuning et al 2009;Krepkowski et al 2010;Volland-Voigt et al 2010). By measuring stem diameter increase and shrinkage over the seasons, insight in intra-annual growth dynamics can be obtained.…”
Section: Periodicity In Tree Growth and Detection Of Tropical Tree Ringsmentioning
confidence: 99%
“…Tree-ring analysis in Cedrela was successfully applied in several studies that demonstrated the annual formation of their growth rings and their dendrochronological potential (Brienen and Zuidema 2005;Bräuning et al 2009;Dünisch et al 2002a;Worbes 1999). In tropical regions these species have tree rings visible to the naked eye (López 2011), which facilitates the crossdating process.…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies have validated these findings and have raised important implications for the future of management decisions involving tropical forests (e.g. worBes 1989;1995;2002;sTahle 1999;dünisch and monTóia 2003;FichTler and clark 2003;Brienen and Zuidema 2005;Brienen and Zuidema 2006;Therrell et al 2006;Baker and BunyaveJchewin 2006;BräuninG et al 2009;lewis et al 2009;roZendaal et al 2009;Brienen et al 2010;héraulT et al 2010;roZendaal et al 2010;TroueT et al 2010;roZendaal and Zuidema 2011;wils et al 2011;donG et al 2012;Zuidema et al 2012;locosselli et al 2013;alTman et al 2013;de ridder et al 2013;Zuidema et al 2013;GroenendiJk et al 2014;locosselli et al 2016;colomBaroli et al 2016;volland et al 2016).…”
Section: Introductionmentioning
confidence: 89%